2016
DOI: 10.1016/j.eats.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Midshaft Clavicle Fractures: Application of Local Autograft With Concurrent Plate Fixation

Abstract: Abstract:Currently, open reductioneinternal fixation using contoured plates or intramedullary nails is considered the standard operative treatment for midshaft clavicle fractures because of the immediate rigid stability provided by the fixation device. In addition, autologous iliac crest bone graft has proved to augment osteosynthesis during internal fixation of nonunion fractures through the release of osteogenic factors. The purpose of this article is to describe a surgical technique developed to reduce dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…However, in recent years, some literature reports have shown that there are some major drawbacks in autologous transplantation, such as pain in the donor region, hematoma in the bone graft area, nerve damage and paresthesia, and even infections. In addition, limited bone mass, prolonged operation time and extra bleeding during surgery add to the disadvantages of autologous bone grafting 36,37. Furthermore, the bone graft may also have risks of position changing and bone absorbing, sclerosis and necrosis, still resulting in bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, some literature reports have shown that there are some major drawbacks in autologous transplantation, such as pain in the donor region, hematoma in the bone graft area, nerve damage and paresthesia, and even infections. In addition, limited bone mass, prolonged operation time and extra bleeding during surgery add to the disadvantages of autologous bone grafting 36,37. Furthermore, the bone graft may also have risks of position changing and bone absorbing, sclerosis and necrosis, still resulting in bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…As they note, their technique is limited by the quantity of local bone graft available and the fact that drilling may cause heat-induced osteonecrosis and influence the quality of the bone graft as well. 17 Our technique features several advantages compared with the previously described literature ( Table 3 ). We endorse a standard shoulder arthroscopy set-up with minimal modifications in the prepping and draping to incorporate the clavicle.…”
Section: Discussionmentioning
confidence: 98%
“…14 Although the use of free vascularized bone grafting has been reported for the treatment of clavicle fracture nonunion, this is predominantly reserved for larger defects in the revision setting. 15,16 Slette et al 17 recently described a technique using local bone graft harvest for ORIF of the clavicle. They recommend careful collection of the bony remnants during ORIF of the clavicle from the drill holes and the drill flutes prior to placement of the screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation